2021
DOI: 10.3389/fendo.2021.736077
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anthropometric Indices With the Development of Diabetes Among Hypertensive Patients in China: A Cohort Study

Abstract: BackgroundPatients with comorbidity of hypertension and diabetes are associated with higher morbidity and mortality of cardiovascular disease than those with hypertension or diabetes alone. The present study aimed to identify anthropometric risk factors for diabetes among hypertensive patients who were included in a retrospective cohort study.MethodsHypertensive adults without diabetes were recruited in China. Demographic, clinical, biochemical, and anthropometric indices were collected at baseline and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Unsurprisingly, consistent with other studies [19][20][21], FPG was the strongest contributor to the models. We also found that the contribution of WC was higher than that of BMI in both forecast periods, which modestly supports the view that the reliability of BMI for determining obesity, a well-known major risk factor for diabetes, was questioned [22] because BMI did not distinguish fat mass from lean mass [23] and WC represented central obesity.…”
Section: Discussionsupporting
confidence: 77%
“…Unsurprisingly, consistent with other studies [19][20][21], FPG was the strongest contributor to the models. We also found that the contribution of WC was higher than that of BMI in both forecast periods, which modestly supports the view that the reliability of BMI for determining obesity, a well-known major risk factor for diabetes, was questioned [22] because BMI did not distinguish fat mass from lean mass [23] and WC represented central obesity.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, WWI can draw out the benefits of WC and weaken the correlation with BMI, thus reflecting mainly weight-independent centripetal obesity. Several studies have demonstrated the positive association between WWI with new-onset hypertension, diabetes, and even the all-cause and cardiovascular mortality (9)(10)(11). Kim et al confirmed that WWI could be an indicator of fat and muscle composition changes related to aging commonly applicable to all race/ethnic groups (12).…”
Section: Introductionmentioning
confidence: 98%
“…The Waist to Hip Ratio (WHR) and Waist to Height Ratio (WHtR) were calculated by dividing WC by HC and Height (cm), respectively. Other Anthropometric indices were calculated based on the following formulae [ 22 , 23 ]:…”
Section: Methodsmentioning
confidence: 99%